Identification and Enrichment of Indonesian Zeolite using Cation Flotation Method - Muhammad Hikam; Endang Asijati (Institut Teknologi Bandung, 2001)
The cation flotation method was employed to enrich the A-modernite fraction by observing the change of the mixture density, pH, type and concentration of collector and concentration of HF as a function of the floated quantity of this A-morderite. X-ray diffraction analysis using Shimadzu XD-D1 was conducted to examine the specimens for several variations and settings. The d-spacing identifications were done by comparing the experimental data with the ICDD database and then quantitative analyses were performed. Before the treatment, the existence of A-mordenite in this natural product was confirmed, it has space group Fd3m with lattice parameters a = (24.46 ± 0.96) Å. The average weight concentration before the treatment was 41,02%. The remaining mineral was identified as epistilbite Ca3Si9Al3O24.8H2O, clinoptilolite [KNa2K2] Al2Si10O247H2O and B-mordernite [CaNa2K2]Al2Si10O24.7H2O. After the treatment, higher concentration of A-mordenite was obtained by setting a higher collector concentration, lower HF activator, and pH value to the value 5.0. The highest concentration of A-mordenite was achieved when the setting was 66.45%. The crystallographic structure remained the same since there were neither violent chemical reactions nor heating in all the processes.